The language picture of the world as a reflection of the reality (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with the questions which concern the language picture of the world, the history of views on this problem is analysed. The language picture appears as a contemplation of the world, as of an every single man, so as of the whole ethnic group. It is a result of the world’s perception and comprehension which is kept in the language.
Keywords: the language picture of the world; conceptualization; cognition; environment; sensation of the world